Salivary Glands New Approaches in Diagnostics and Treatment - Adadan Güvenç, Işıl (IntechOpen, 2019)
Saliva is a complex fluid that maintains oral health and has many physiological functions. It is a noninvasive diagnostic fluid as well. Lately, salivary diagnostics has proven its potential to reach clinical practice in the near future for the early detection, diagnosis, and monitoring of various diseases. Salivary Glands - New Approaches in Diagnostics and Treatment is a comprehensive reference, which brings together information on salivary secretion and its disorders, the novel salivary diagnostic methods for numerous diseases, and new techniques in the treatment of salivary diseases. This book contains information for a diverse audience, including dentists, oral biologists, experimental biologists, molecular biologists, oncologists, radiologists, oral and maxillofacial surgeons, and otorhinolaryngologists.